Effect of Hydrogen Sulphide Containing Mineral Water on Experimental Osteoporosis in Rats - Popović, Tamara; Amidžić, Ljiljana; Čeko, Mile; Marković, Siniša; Škrbić, Ranko (Scripta Medica, 2022)
Background/Aim. Sulphur mineral water is widely used in the treatment of musculoskeletal diseases. Hydrogen sulphide is an important regulator of bone metabolism and its application in the treatment of osteoporosis is intensively researched. The aim of this study was to analyse biochemical and histological effects of H2S containing mineral water of “Mlječanica” spring on ovariectomy-induced experimental osteoporosis in rats. Methods. In this experiment a 14-week-old Wistar female rats were used. The animals undergone bilateral ovariectomy (OVX groups) as an experimental model for oestrogen-deficient osteoporosis. After six weeks, animals were divided into control and the experimental group. Rats from the experimental group treated with H2S (SW group) containing mineral water ad libitum during five weeks. Biochemical parameters for monitoring sulphur water effects were concentration in serum of osteocalcin, alkaline phosphatase, calcium and phosphorus. Histological analyses of the left tibia coloured with haematoxylin-eosin were carried out. Results. Regarding the biochemical parameters, a statistically significant increase was observed in the OVX group for osteocalcin, alkaline phosphatase calcium and phosphorus compared to the sham-operated (CNT) group (p < 0.01). In SW + OVX, alkaline phosphatase was statistically significantly decreased (p < 0.01) and serum osteocalcin and phosphorus increased (p < 0.01). Calcium values were increased without significance. In the OVX + SW group, histological analyses showed numerous osteoblasts along the trabecular endosteum and the growth of young chondrocytes in the central bone zone and their migration to the peripheral parts. Conclusion: Drinking the H2S containing “Mlječanica” mineral water has led to decreased alkaline phosphatase, increased osteocalcin and phosphorus concentration in serum and stimulated the bone reparation in osteoporotic rats.